PENGARUH PENGGUNAAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR IPAS MATERI RANTAI MAKANAN KELAS V SDN WEGOKNATAR - Novenrius Sini Timba, Frederiksen; N. Sini Timba, Frederiksen; Kristiani Maria, Sonya (Universitas Cokroaminoto Palopo, 2024)
This study aims to determine the effect of differentiated instruction on the learning outcomes of science (IPA) in the topic of food chains for fifth-grade students at SDN Wegoknatar. Differentiated instruction was implemented to accommodate the varying abilities of students, with the expectation that it would improve their understanding and learning outcomes. The research design employed is a quasi-experimental design with a pretest-posttest control group. The subjects of the study consisted of two classes: the experimental class, which was taught using differentiated instruction, and the control class, which used conventional teaching methods. Data were collected through pretest and posttest assessments of student learning outcomes. The results showed a significant difference in the learning outcomes between the experimental and control classes, with the experimental class showing greater improvement in learning outcomes. These findings suggest that differentiated instruction can enhance students' learning outcomes in the topic of food chains. The study recommends the use of differentiated instruction as an effective strategy to improve science learning outcomes in elementary school.